Impact of corporate governance and social responsibility on credit risk - AlHares, Aws (Frontiers in Sustainability, 2025)
This study measures the effects of corporate governance (CG) and corporate social responsibility (CSR) on bank risk. The data were collected from DataStream from 2010 to 2021 from the World Development Indicators. The analysis in this study utilized the fixed effects model, where multiple parameters were found to be negatively associated with credit risk, such as board independence, board size, and board meetings. By contrast, ownership concentration can positively affect bank credit risk. Additionally, applying CSR can decrease credit risk. Finally, this study sheds light on the implementation of governance, which leads to a reduction in credit risk. Our findings have significant policy implications for credit risk management in the banking sector, emphasizing that a one-size-fits-all approach is inadequate. Governance practices effective in one context may not produce the same outcomes in another. The evidence suggests that banks in emerging economies are making meaningful strides in establishing and strengthening effective governance frameworks.